From Two Republics to One Divided : Contradictions of Postcolonial Nationmaking in Andean Peru - Thurner, Mark (Book collections on Project MUSE., 1997)
"Culmination of author's work on the Peruvian peasantry and its conflicts with the Eurocentric view of nationhood held by the majority of Peru criollo leadership. An especially important book for 19th-century specialists as well as those scholars examining the evolution of the role of the indigenous population in Peruvian society. As in item #bi 97012022#, author focuses on the 1885 Atusparia rebellion, which suggests a pragmatic and selective approach to Andean politics that cannot be categorized within the context of the assumed evolution of the liberal nation-state nor the subsequently more dominant dependency theories. Intelligent study contributes significantly to Andean peasant politics during Peru's formative years. The work would have benefitted from a separate bibliography"--Handbook of Latin American Studies, v. 58.